Protective potential of Persea americana mill. var. americana (AVOCADO)seed extract on Gentamicin-induced Nephrotoxicity in Mus musculus (Albino Mice). - Nabayra, Alvin D. J. (2009)
The study aimed at determining the protective potential of the avocado seed extract against gentamicin induced nephrotoxicity in albino mice. Histopathological results were obtained in order to verify such a protective potential. Significant structual changes in the mice kidneys were caused by high dosage of gentamicin on T1. However, no damage was noted during the histological evaluation of the kidney slides during T0. When compared, glomerulus and renal tubules remain intact in T0 against the damaged tubules and ruptured glomerular capsules in T1. Attempts at establishing the mode of protection of the avocado seed extract was not determined in the study. With these, there is a need to identify the chemical compounds found in the avocado seed and their mode of effect on the cell. Other plant species, likewise, could also be determined which could have the potential of providing protection against nephrotoxicity. In the process, other organs could also be subjected to examination in order to find out whether or not the extract affects not only the kidneys.